Distraction : Problems of Attention in Eighteenth-Century Literature - Phillips, Natalie M. (Book collections on Project MUSE., 2016)
Early novel reading typically conjures images of rapt readers in quiet rooms, but commentators at the time described reading as a fraught activity, one occurring amidst a distracting cacophony that included sloshing chamber pots and wailing street vendors. Auditory distractions were compounded by literary ones as falling paper costs led to an explosion of print material, forcing prose fiction to compete with a dizzying array of essays, poems, sermons, and histories. In Distraction, Natalie M. Phillips argues that prominent Enlightenment authors-from Jane Austen and William Godwin to Eliza Haywood and Samuel Johnson-were deeply engaged with debates about the wandering mind, even if they were not equally concerned about the problem of distractibility. Phillips explains that some novelists in the 1700s-viewing distraction as a dangerous wandering from singular attention that could lead to sin or even madness-attempted to reform diverted readers.